Descriptive Study of Organophosphorus Poisoning in the Post Graduated Hospital Khost Afghanistan - Sajad, Ezatullah; Sarwari, Jawid Shah; Sabirzai, Mohammad Kamil; Sharif, Sherzad Gul (Journal for Research in Applied Sciences and Biotechnology, 2024)
Organophosphorus poisoning is an acute intoxication that occurs when certain insecticides (karbofos, chlorophos, thiophos) or chemical warfare agents (sarin, soman, VI gases) enter the body through inhalation, transdermal or oral intake. Poisoning with them accounts for 1-2% of the total number of acute toxicoses. (1) The poison is able to penetrate the skin without damaging it. At high concentrations of the xenobiotic, pathological symptoms appear within a few minutes. Organophosphorus compounds dispersed in the air form a persistent cloud located near the surface of the earth, which persists for 4-6 hours. Military chemical agents are capable of maintaining toxic concentrations for several days. Lethal doses are vary greatly depending on the properties of the particular compound. Methodology: Our study is a descriptive case series conducted in the year 1399 (1st 6 months). Among 1274 inpatients that were admitted in Khost post graduated Hospital during that time, 50 patients were diagnosed with organophosphorus poisoning. Goals of Research: Determining the Frequency and Pattern of Organophosphorus poising in Khost post graduated Hospital during 1399 (1st 6 month) hejri shamsi.